Meningkatkan Kemampuan Berpikir Kritis Melalui Pengembangan Model OIDDE Berbantuan Studi Kasus pada Mata Kuliah Pendidikan Pancasila - Fitria, Mega Risky (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to develop an orientation, identify, discuss, decisive, and engage in behavior (OIDDE) model with the help of appropriate and practical case studies to improve students' critical thinking skills in the Pancasila Education course at the State University of Malang. This study utilized the stages of Borg & Gall's research and development. The study results showed that the developed model was valid and practiced for improving students' critical thinking skills. The model's validity was obtained from the expert validation test of the learning model, which got an average score of 96,9. The material expert validation test scored 84.4, and the semester study plan (RPS) validity of 82.7. The practicality of the model tested in small groups obtained a score of 84.6 from lecturers and 79 from students, while the large group trial obtained a score of 85 from lecturers and 84 from students. The average student's critical thinking ability reached a score of 84, which was originally 74. It indicated a significant change in students' critical thinking skills before and after implementing the developed learning model.